DRAG FORCE ANALYSIS OF EXTERNAL QUARK IN ROTATING AND STRONGLY INTERACTING QUARK GLUON PLASMA (QGP) USING STRING THEORY - Ardian Nata Atmaja (Pusbindiklat - LIPI, 2012)
In this paper, it is analyzed drag force of a quark in a rotating and strongly coupled Quark Gluon Plasma(QGP) by considering the motion of a string under background metric of rotating Banados-Teitelboim-Zanelli(BTZ) black hole. The non-trivial solution of string motion under rotating BTZ black hole depends on a constantmomentum conjugate which is fixed physically in all space. The drag force is characterized by the black hole’sparameters (curvature, mass and angular momentum) and angular velocity of the string. Moreover, it is also foundan external force term proportional to the angular momentum of the black hole in non-relativistic limit.